Cultural Anthropology - Kottak, Conrad Phillip (New York, 2009)
Since 1968, I've regularly taught Anthropology 101 (Introduction to Anthropology) to a class of 375 to 550 students. Constant feedback from students, teaching assistants, and my fellow instructors keeps me up to date on the interests, needs, and views of the people for whom this text is written. I continue to believe that effective text-books are rooted in enthusiasm and enjoyment of one's own teaching experience
Keywords: Ethnology